Efficacy of the visual cognitive assessment test for mild cognitive impairment/mild dementia diagnosis: a meta-analysis - Hsu, Jui-Hung; Liu, Chien-Cheng; Chen, I-Wen; Wu, Jheng-Yan; Huang, Po-Yu; Liu, Ting-Hui; Hung, Kuo-Chuan (Frontiers in Public Health, 2023)
Background: Mild cognitive impairment (MCI) is an intermediate stage between normal ageing and dementia. The early identification of MCI is important for timely intervention. The Visual Cognitive Assessment Test (VCAT) is a brief languageneutral screening tool for detecting MCI/mild dementia. This meta-analysis evaluated the diagnostic efficacy of the VCAT for MCI/mild dementia.Methods: Medline, Embase, Google Scholar, and Cochrane Library were searched from their inception until August 2023 to identify studies using VCAT to diagnose MCI/mild dementia. The primary outcome was to assess the diagnostic accuracy of the VCAT for detecting MCI/mild dementia through area under the receiver operating characteristic curve (AU-ROC) analysis. The secondary outcome was to explore the correlation between VCAT scores and MCI/mild dementia presence by comparing scores among patients with and without MCI/mild dementia. Pooled sensitivity, specificity, and area under the curve (AUC) were calculated.Results: Five studies with 1446 older adults (mean age 64-68.3 years) were included.The percentage of participants with MCI/mild dementia versus controls ranged from 16.5% to 87% across studies. All studies were conducted in Asian populations, mostly Chinese, in Singapore and Malaysia. The pooled sensitivity was 80% (95% confidence interval [CI] 68-88%) and the specificity was 75% (95% CI 68-80%). The AU-ROCC was 0.77 (95% CI 0.73-0.81). Patients with MCI/mild dementia had lower VCAT scores than the controls (mean difference -6.85 points, p<0.00001).Conclusions: VCAT demonstrated acceptable diagnostic accuracy in distinguishing MCI/mild dementia in cognitively normal older adults. As a language-neutral and culturally unbiased tool, the VCAT shows promise in detecting MCI/mild dementia.Further studies in non-Asian populations are required.